2016
DOI: 10.1038/ismej.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Warming and nutrient enrichment in combination increase stochasticity and beta diversity of bacterioplankton assemblages across freshwater mesocosms

Abstract: The current climate warming and eutrophication are known to interactively threaten freshwater biodiversity; however, the interactive effects on lacustrine bacterioplankton diversity remain to be determined. Here, we analyzed the spring bacterioplankton community composition (BCC) in 24 outdoor, flow-through mesocosms (mimicking shallow lake environments) under 3 temperature scenarios and 2 nutrient regimes. Our results revealed that neither long-term warming (8.5 years) nor nutrient enrichment had significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 71 publications
(102 reference statements)
7
50
1
Order By: Relevance
“…In summer seawater, we found lower percentages of Actinobacteria at sites with more thermal effluents, which was probably related to the obviously increased relative abundance of Cyanobacteria. This finding is consistent with previous reports showing negative relationships between the relative abundances of Cyanobacteria and Actinobacteria in aquatic ecosystems (19,41). Furthermore, Bacteroidetes have been found to be likely to attach to marine eukaryotic algae or animals (42,43).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In summer seawater, we found lower percentages of Actinobacteria at sites with more thermal effluents, which was probably related to the obviously increased relative abundance of Cyanobacteria. This finding is consistent with previous reports showing negative relationships between the relative abundances of Cyanobacteria and Actinobacteria in aquatic ecosystems (19,41). Furthermore, Bacteroidetes have been found to be likely to attach to marine eukaryotic algae or animals (42,43).…”
Section: Discussionsupporting
confidence: 92%
“…Among all the environmental factors examined, the spatially structured temperature created by thermal effluents played the strongest role in determining bacterioplankton metacommunity structure across thermal gradients in both seasons studied. Differences in traits cause different bacterial populations to have different sensitivities to temperature during their growth processes (44)(45)(46)(47); thus, temperature is one of the most important factors in shaping bacterioplankton community structure (19,35,48). This finding was further confirmed by the positive linear correlations between BCC dissimilarities and temperature differences in any pairwise comparison of sampling sites.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The underlying mechanisms are unclear, but include the increased likelihood for priority effects at higher productivity because growth of early colonizers is promoted under such conditions (Steiner, 2014;Fukami, 2015). Support for similar processes operating in natural bacterial communities comes from two experimental studies from soil and freshwater bacterial communities (Ren et al, 2017) where fertilization increased the importance of stochastic processes in relation to deterministic processes, in the latter case in particular in combination with warming. On the contrary, Langenheder et al (2012) found in a field survey that species sorting processes were important in bacterioplankton communities at times when productivity in the metacommunity was high.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Ren et al. () found that spring bacterioplankton community composition shifted significantly under enhanced warming and nutrient‐enriched conditions. Although the above studies provide an exceptional opportunity to gain insight into the controlling factors of bacterioplankton community composition and structure in inland aquatic ecosystems, factors related to bacterioplankton diversity and communities in the city‐river section, reservoir area, and outflow area of dammed karst rivers are still unknown.…”
Section: Introductionmentioning
confidence: 99%